La convivencia social post-covid-19 en el nivel de educación inicial 2 de la Unidad Educativa Cristiana Nazareno, ciudad Riobamba, provincia Chimborazo. - Montero Sánchez, Amy Katherine (2023)
The present investigation under the theme “post-covid-19 social coexistence in the cristiana nazareno education until, in the riobamba city, chimborazo province.”, has as main objective to determine the condition of post-covid-19 social coexistence at the level of initial education 2, since it considered as the reciprocal respect between individuals, gadgets and the environment in which they live, in addition to allowing children to learn patterns that facilitate their social relationships, promoting the development of attitudes of respect and empathy towards themselves and those around them. It is also necessary to mention the great importance of coexistence within the scope of personal and social development and the development of social relationships. Reason for which surveys applied that showed the relationship of coexistence between peers after a pandemic event caused by the COVID-19 confinement; the results being exposed in a descriptive-narrative way with a qualitative approach finding novelties in the components of safety and trust when the child had to return to face-to-face; category that can lead to specialized studies of conduct and behavior in childhood.